RAPID DETECTION OF MULTI DRUG RESISTANCE AMONG MULTI DRUG RESISTANT TUBERCULOSIS SUSPECTS USING LINE PROBE ASSAY - Dubey, Manoj Kumar; Bhardwaj, Uma; Hanif, M; Kk, Chopra; Khanna, Ashwani; Saini, Sanjeev; Dwivedi, Kaushal Kumar; Vashistha, Himanshu; Sidiq, Zeeshan; Ahmed, Vasim; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: GenoType MTBDRplus line probe assay (LPA) is developed for performing drug susceptibility testing (DST) for Rifampicin (RIF) and isoniazid in sputum specimens from smear-positive pulmonary tuberculosis (TB) patients and revised national TB control Programme (RNTCP) has endorsed LPA for the diagnosis of multi drug resistant TB (MDR-TB). This study was conducted to assess the potential utility of LPA for MDR-TB patient management. Methods: MDR-TB suspects under RNTCP PMDT criteria C referred from different districts in Delhi state were included in the study January 2013 to December 2014. Sputum specimens found acid-fast bacilli positive by fluorescent microscopy were processed for LPA. Results: Out of 3062 specimens, 2055 (67.1%) MDR-TB suspects were read as positive and specimens from 1007 (32.9%) suspects were read as negative in sputum smear microscopy. Out of 2019 specimens valid LPA results, 1427 were found to be pan-sensitive, 280 were MDR-TB, 40 were RIF monoresistant, 183 were Isoniazid (INH) monoresistant, and 89 specimens were found negative for Mycobacterium tuberculosis. Conclusion: Routine use of LPA can substantially reduce the time to diagnosis of RIF and/or INH-resistant TB and can hence potentially enable earlier commencement of appropriate drug therapy and thereby facilitate prevention of further transmission of drug resistant strains. Keywords: Multi drug resistant tuberculosis, Line probe assay, Rifampicin, Isoniazid.